Overview Of The Risk Of Falls In The Elderly At The Dharma Bhakti Kasih Nursing Home in Surakarta - Devi Natasya Faradilla; Ika Silvitasari (CV. AFDIFAL MAJU BERKAH, 2026)
Falls are a major health problem in the elderly, contributing to high rates of injury, decreased independence, and increased need for long-term care. Falls not only impact physical health but also create a fear of activity, thus worsening the quality of life for the elderly. Increasing age, decreased musculoskeletal function and balance, and unsafe living conditions are factors that increase the risk of falls. This study aims to determine the description of the risk of falling in the elderly at the Dharma Bhakti Kasih Surakarta Nursing Home. The research design used is descriptive quantitative with observation method. The number of respondents was 30 elderly selected using purposive sampling technique. This research instrument used the Morse Fall Scale (MFS) to assess the level of fall risk. Results: The study shows that based on the characteristics of respondents based on initial age 60-75 years (50%), the majority of gender is female 18 respondents (60%). Most of the elderly have a low risk of falling (50%), no risk of falling (40%) and only a small portion have a high risk of falling (10%). The majority of elderly have a low risk of falling (50%) of 30 respondents.